Industry 4.0: the impacts, challenges and perspectives for the administrator (Research, Society and Development, 2020)
A basic feature of Industry 4.0 is to connect factory floor activities and their systems to smart grids, having their decisions controlled autonomously, being able to identify and correct faults automatically, storing knowledge and gaining predictive capacity, reducing downtime in your chain of value. The purpose of this investigation is to study the impacts, challenges and perspectives of Industry 4.0 for the administrator. An exploratory and explanatory investigation was adopted as a research method, in order to develop, clarify concepts and ideas with the searchable hypotheses, seeking to register, analyze, classify and interpret the studied phenomena, with the central concern of knowing their determining factors for corporations. . The results indicate that organizations must remain attentive to the concept and how it will impact in the medium and long term in their business, indicating the importance of investments in new technologies. The conclusions indicate that companies can benefit from cost reduction, energy savings, increase in network security, environmental conservation, reduction of errors, end of waste, transparency in business, increase in quality of life, customization in scale and unprecedented, among others. Therefore, it is necessary to develop a holistic and systemic vision at all levels of companies, changes in organizational culture and management style.